(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
The research highlights on the philosophical views of Hume upon the historical rise of belief in religion and the graduation from Poytheism to the religion of monotheism. And standing on the natural sources of religious feeling and the natural and normal history of religion and rejecting the sacred history of it. Research also poiats to the limitaions of the mental approach in thume’s view of the priests to prove the existence of God. That Retionalists who were still claming a certain knowledge of the truths of faith, arousing suspicion of the principles of religion and The agonostic consequences that Hume concluded.